Aristotle, the collected papers of Joseph Owens - Owens, Joseph, 1908-2005 (State University of New York Press, 1981)
Companion vol. to the author's St. Thomas Aquinas on the existence of God. "Complete bibliography of Joseph Owens, C. Ss. R., M.S.D.": pages [228]-239. Includes bibliographical references and indexes